2014
DOI: 10.1136/bcr-2013-201533
|View full text |Cite
|
Sign up to set email alerts
|

Perforated isolated jejunal diverticulum: a rare aetiology of acute abdomen

Abstract: SUMMARYIn the absence of trauma, perforated jejunal diverticulum ( JD) is a rare entity. Perforated isolated JD is rarer. We report a case of perforated isolated JD in a 55-year-old woman who presented with features of peritonitis and had no history of trauma. Resection and anastomosis of the involved jejunal segment was performed. BACKGROUND

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 11 publications
0
18
0
Order By: Relevance
“…About 10-30% of patients develop complications like perforation, obstruction, hemorrhage and diverticulitis [2,3]. There are very few case reports in the literature of jejunal diverticulosis presenting with perforation [6,7,9,10] Our patient too remained asymptomatic, until he presented with acute abdomen because of perforated diverticuli.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…About 10-30% of patients develop complications like perforation, obstruction, hemorrhage and diverticulitis [2,3]. There are very few case reports in the literature of jejunal diverticulosis presenting with perforation [6,7,9,10] Our patient too remained asymptomatic, until he presented with acute abdomen because of perforated diverticuli.…”
Section: Resultsmentioning
confidence: 95%
“…in India, We have found seven cases of jejunal diverticulosis reported in India, five of them presented with complications like perforation, gastrointestinal bleeding and intestinal obstruction [3,[5][6][7][8][9][10]. In this regard, a recent cadaveric study of duodenum conducted in South India showed the prevalence of 4.2% for duodenal diverticulosis [11].…”
Section: Resultsmentioning
confidence: 99%
“…They usually arise along with other diverticulae elsewhere in the abdomen such as the colon in up to 75% (30-75%) of cases which may suggest a potential connective tissue disorder [6,7]. They are rarely solitary (1). Their size varies between a few millimeters to greater than ten centimeters [2].…”
Section: Discussionmentioning
confidence: 99%
“…Computed tomography is the most useful diagnostic imaging modality in diagnosing jejunal diverticula most often demonstrating jejunal thickening, inflammation or localized abscess formation [1,3,5]. Nevertheless currently, direct visualisation of diverticula via explorative laparoscopy or laparotomy is the only way of confirmation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation